Challenges in the management of early versus late presenting congenital diaphragmatic hernia in a poor resource setting - Abubakar Auwal; Bello Mustapha; Chinda John; Danladi Kwari; Umar Ibrahim (Wolters Kluwer Medknow Publications, 2011)
Background: Despite the advances in management, congenital diaphragmatic hernia (CDH) has continued to pose a significant challenge to paediatric surgeons. This is amplified in a setting like ours where there is a dearth of facilities to cope with the problem of CDH. This study was undertaken to highlight the peculiarities of the management of CDH in a poor resource setting. Methods: All confirmed cases of CDH were prospectively documented from 2003 till date. Results: Seven children were treated from 2003 till date. The diaphragmatic defect was on the left side in six (83.8%) and on the right side in one (17.7%). All the patients had primary closure of the defect without patch via an abdominal approach. The three patients presenting at birth died while the remaining four patients survived. Conclusion: With inadequate neonatal intensive care facilities, the severe early presenting CDH has a dismal prognosis. In contrast, the late presenting CDH poses more diagnostic challenges; but once identified and appropriate treatment instituted, it has an excellent prognosis. We recommend that physicians should include CDH in the differential diagnosis of patients with birth asphyxia and in patients with chronic respiratory symptoms with failure to thrive.